Multilingual school children’s use of Icelandic in daily life - Pálsdóttir, Auður; Ólafsdóttir, Sigríður; Karlsson, Örn Þór (Menntavísindasvið Háskóla Íslands, 2024)
This research aims to collect information on how multilingual school children in Grades 6–10 use Icelandic, English, and home language, how they evaluate their skills in these languages, and to test relations between language use and reading habits with their estimated Icelandic language skills. The incentive is to enable teachers and school authorities to better organise the support and instruction that are provided to multilingual children. The research data includes individual interviews with 78 multilingual students in Fellaskóli Reykjavík in spring 2022. This group is 54% of all multilingual students in Grades 6–10 and approximately 43% of the total number of learners at this age in Fellaskóli. In Iceland, the vast majority of children start preschool at two years of age, and even younger, where they spend eight to nine hours a day, five days a week. In pre- and compulsory school, Icelandic is the main language, whereas, outside school, English is increasingly being used by youth, mainly on the internet. An increasing number of learners speak a third language with their families. Thus, bilingualism is the norm in Iceland, and multilingualism is very common. Despite long school days, the evidence indicates that multilingual children do not learn much Icelandic during the pre-school years (Aneta Figlarska et al., 2017; Hjördís Hafsteinsdóttir et al., 2022; Sigríður Ólafsdóttir & Ástrós Þóra Valsdóttir, 2022). Therefore, they start compulsory school with weak Icelandic language proficiency. Over the next 10 years that follow, the gap between first-language Icelandic learners and multilingual learners tends to grow with each school year (Elín Þöll Þórðardóttir, 2021; Sigríður Ólafsdóttir et al., 2016). According to PISA 2022, 63% of immigrants in Iceland did not reach the minimum level of reading literacy. It is evident that Icelandic schools have to reconsider how they can support and teach multilingual youth and focus better on Icelandic language use. In compulsory school, students must read subject ...